2020
DOI: 10.1016/j.dsx.2020.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes self-management amid COVID-19 pandemic

Abstract: Background and aims: COVID-19 pandemic has challenged the physician-centered approach of diabetes care in India that is primarily based on routine clinic visits. We aim to review the various aspects of patient-centered care via diabetes self-management education based on available literature. Methods: This is a narrative review using Pubmed, EMBASE and Google Scholar search till March 29, 2020. Search terms were "COVID-19", "diabetes self-care", "diabetes self-management education", "DSME", "diabetes self-mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
222
0
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(240 citation statements)
references
References 21 publications
4
222
0
14
Order By: Relevance
“…COVID e 19 pandemic has affected the psychological health of normal people as well as the people with diabetes. The steps advised as preventive measures like social distancing & lockdown in breaking the chain of spread of the virus have increased the stress and anxiety among the people [7].…”
Section: Discussionmentioning
confidence: 99%
“…COVID e 19 pandemic has affected the psychological health of normal people as well as the people with diabetes. The steps advised as preventive measures like social distancing & lockdown in breaking the chain of spread of the virus have increased the stress and anxiety among the people [7].…”
Section: Discussionmentioning
confidence: 99%
“…Good glycemic control should be targeted as it would help boost the innate immune system [4,35]. However, widespread nationwide lockdowns would curtail their routine in-clinic visits, limit their physical activity, alter their food habits and adversely affect their psychological health; all these would ultimately lead to poor glycemic control [36]. Infact, a recent study from China had shown that elderly subjects with type 2 diabetes mellitus had higher fasting blood glucose during the COVID-19 pandemic [37].…”
Section: Management Of Diabetes Mellitus Amid Covid-19 Pandemicmentioning
confidence: 99%
“…Rogers et al [20] argue convincingly that the role of podiatry in the coming months and years as the full impact of COVID-19 plays out is to stand up and take a leading role in managing lower limb health in people with diabetes. Banerjee et al [65] identified the barriers to diabetes selfmanagement during the pandemic, and suggested possible solutions to overcome these. South Africa has a serious shortage of podiatrists and inadequate provision of foot care in both private and State Health Services.…”
Section: Vulnerable Patients: Diabetes Older Peoplementioning
confidence: 99%